(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, eMeO GdfLaj, eMeO MSf Hf HGbQ, J (B1266(3g` (B1850(3es
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdELGQI, GdJj gj Ydi fMh eG SeYJg aj daX GdHjY ef Cf GdCUM chfgG fbd GdefaYI dG GdYbO hdG GdGfJbGd ceG YQaJg aj cJGH GdHjY eaUdGs
(3BNQgG (B:s
(3BNQgG(B: (3hdh cGf aj CMO (B.. (3ef de jMSf GdQej HWd GdYbO ajg haj ebGHdg hM jJNjQ cd ef (B.. (3aj aSN GdYbO dchfg M cJHYV GdUabI hcjajI GdZdHI Hjf (B.. (3Ydi MSH eG jTJQWhfg hjJabhf YdjgG Hjfge(B.s
(3GdfSNI ebGHdI Ydi eShOI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 214s
(3GdPQjYI, L (B5: 196s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis